(untitled) (Eurasian Journal of Humanities and Social Sciences, 2026)
This article provides a deep scientific analysis of the hierarchical system of syntactic units of the Uzbek language, their practical manifestations in oral and written speech, methodological and communicative-pragmatic functions. The article reveals the grammatical and pragmatic functions of syntactic sentences. Also, innovative and pedagogical-didactic principles of teaching syntactic units in secondary schools within the framework of continuous education are substantiated.